Viewpoint: Is critical art librarianship actually a thing?. (April 2019) - Appleton, Leo
Abstract : If I'm being honest I still feel as though I am a bit of an imposter in the world of art librarianship. I often feel as though I have a very conservative, corporate and conformist approach to librarianship within the art library environments in which I work. I also often feel naïve when it comes to discussing and affirming 'what makes art librarianship different?' Acknowledging such naivety, I will also openly admit that until last year I had not heard of 'critical librarianship' as a concept, let alone 'critical (art) librarianship', which is how I was introduced to it at a day-long conference held by colleagues from the University of the Arts London in 2018 at Chelsea College of Arts.